Valorização de OAU por conversão em biodiesel catalisada por líquidos iónicos - Diniz, Heloísa Oliveira Resende (2022)
Biodiesel is a source of energy that can replace fossil diesel by reducing environmental impacts. It consists of a mixture of alkyl esters of long chain fatty acids and is produced by converting vegetable oils or animal fats by transesterification or esterification reactions. Due to the high cost of the conventional raw materials, it is viable to reduce the final price of biodiesel by using oil sources that do not compete with the food market, such as waste cooking oils. However, these oils show high levels of free fatty acids, which can bring about problems to the classic biodiesel production process. To overcome these problems, ionic liquids (IL) are used as catalysts and can be recovered and reused. Thus, the objectives of this work are to study the production of biodiesel by applying 1-methylimidazolium hydrogen sulphate ([HMIM][HSO4]) ionic liquid as a catalyst for esterification/transesterification reactions in samples of residual vegetable oils and to evaluate the maximum number of recovery cycles that can be performed with the IL without significant loss of the reaction yield. Using oleic acid as feedstock, reaction time of 4 hours, temperature of 65° C, molar ratio 1/10 of oleic acid/methanol and 10%wt. of IL relating to oleic acid, an initial conversion of 81.2% was obtained and after six reactions the value dropped to 69.4%. The correlation between FTIR spectra relating to the initial IL and the IL after the sixth reaction cycle was 99.3%, showing that the recovery method is efficient.